Sprinkles enterprise cupcakes - Tan Mustafar, Nur Syakira; Zainudin, Afiqah Aliah; Mohd Asri, Fatin Anisah; Mohamed Ramdan, Nur Ajwa Nadhirah; Sukri, Nur Izzah Balqis; Mohamad Jelai, Nurul Hidayah (2020)
Sprinkles Cafe is a business that introduces a new style of cupcakes to our potential customers. Our product has many varieties of flavours and uniqueness of taste such as Pandan Gula Melaka, Strawberry Fudge and old-time favourites like Vanilla, Red Velvet and Chocolate. We provide a fresh batch of cupcakes at all times during business hours and also will bake upon any customized orders for any occasions. Sprinkles Café will be offered with a variety of flavours, frostings, styles, toppings and decorations. This café will provide a comfortable seating area, allowing customers to dine in and enjoy their favourite cupcakes. Majority of people enjoy delicious cupcakes as cupcakes are a low-priced item. The business starts the operation on 8th April 2020 and expects to expand our business in every state in 10 years. Sprinkle Cafe located at Petaling Jaya, Selangor which is in urban areas and has many populations that can reach our targeted customers. Moreover, we promoted our cafe through social media such as Instagram, Twitter and Facebooks. It is an efficient way to expand our business to a wider range of areas since nowadays most of the customers come from the advertisement through social media which is one of the effective and efficient ways to promote our product without any additional cost needed. Our business operated hours from 10.00 am until 10.00 pm which is 12 hours per day. Furthermore, Sprinkles cafe is registered under the Companies Commission of Malaysia. Sprinkles cafe will be having 2 shifts for the working hours and every worker will be working only 6 hours.